Polymeric Organo-Hydrogels: Novel Biomaterials for Medical, Pharmaceutical, and Drug Delivery Platforms - Aktas, Nahit; Alpaslan, Duygu; Dudu, Tuba Erşen (Frontiers in Materials, 2022)
In recent two decades, tremendous devices and materials such as stents, biomimetic organs, scaffolds, and vessels have been developed for utilization. When such devices are utilized in the body, the side effects or biocompatibility of the materials have to be studied extensively. Interdisciplinary studies carried out have reviled numerous strategies to overcome adverse body reactions against implanted devices. Besides naturally occurring materials such as collagen, chitosan, hyaluronic acid, dextran, various synthetic and modified materials like poly(lactic acid), poly(ethylene glycol), poly(vinyl alcohol), poly(acrylamide) have been accomplished. In this context, progress in polymer science makes hydrogels a valuable candidate for those utilizations. Hydrogels received enormous attention as drug delivery devices because of their unique properties such as soft structure, responsive capabilities based on the functional group attached. Particularly, the developments in synthetic materials have brought out numerous materials for medical and pharmaceutical applications. In recent studies, organo-hydrogels, a branch of hydrogels, have drawn considerable attention over hydrogels because of superior properties such as the coexistence of organic and aqueous phases, viscoelastic bi-phasic natures. They were prepared not only in bulk forms but also in nano-scale dimensions which allow them to be utilized more extensively. These incredible structures provide them with extensive features to be utilized from head to toe in every aspect of health care application. In this short review, we will focus on some of the pioneering perspectives of organo-hydrogels particularly accomplished in clinical therapy and the use of their biodegradable, target-responsive properties as sensing components in novel microscale apertures.